2021
DOI: 10.1007/s11629-021-6853-9
|View full text |Cite
|
Sign up to set email alerts
|

Tourism management in national parks: Šumava and Bayerischer Wald (Bavarian Forest) in the Czech-German borderland

Abstract: Along the Czech-German border there are four national parks, two Czech and two German, arranged in cross-border ‘pairs’. This article focuses on the southern ‘pair’ formed by the parks of Šumava and Bayerischer Wald (Bavarian Forest). The aim is to evaluate and compare tourism organization in their areas, taking into account selected aspects of management: the network of hiking trails with its related infrastructure, transport accessibility, a typology of tourist centers, as well as directions and destinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
1
0
1
Order By: Relevance
“…These include funds from the EU, such as rural development funds, subsidies, cultural conservation and promotion funds, and grants. Only one study reported increased access to certain areas after the end of the communist period as a driver of change (Kołodziejczyk, 2021), while all other supranational factors are in some way funded by the EU (Krzemińska, Dzikowska, Zaręba, & Jarosz, 2018;Zydroń, Kayzer, Fiedler, & Korytowski, 2020). This suggests that the EU employs these strategies as part of its rural development initiatives.…”
Section: Categorymentioning
confidence: 99%
“…These include funds from the EU, such as rural development funds, subsidies, cultural conservation and promotion funds, and grants. Only one study reported increased access to certain areas after the end of the communist period as a driver of change (Kołodziejczyk, 2021), while all other supranational factors are in some way funded by the EU (Krzemińska, Dzikowska, Zaręba, & Jarosz, 2018;Zydroń, Kayzer, Fiedler, & Korytowski, 2020). This suggests that the EU employs these strategies as part of its rural development initiatives.…”
Section: Categorymentioning
confidence: 99%
“…In addition, mismanagement of tourism activities could increase nature degradation in protected areas [Stephenson 1993;IUCN 2005]. Mismanagement of national parks includes lack of conservation plans, inadequate decision-making, and incorrect development of tourism infrastructure [e.g., Stancheva et al 2016;Oleśniewicz et al 2020;Kołodziejczyk 2021]. One might wonder whether national parks are prepared to accommodate these everincreasing numbers of visitors.…”
Section: Tourist Destination Mismanagementmentioning
confidence: 99%
“…The placement of walking sensors can help for reducing the maintenance time of the trail path and the number of users visiting it, and thus, in this way, the local community can know the future trends of the public and adapt accordingly [47]. However, for the people who visit the areas with tourist trail paths to be able to access them, the transportation, the routes, the bus stops as well as the parking of the vehicles should be located close to the starting point of the trail paths, meeting the need of easy transition [48]. Digital mapping of the path trails can help an area to be visited by tourists [49].…”
Section: Literature Reviewmentioning
confidence: 99%